2016
DOI: 10.14238/sp17.3.2015.163-8
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Kadar Feritin Serum dengan Fungsi Kognitif Berdasarkan Pemeriksaan Status Mini-Mental (MMSE) pada Penyandang Thalassemia Anak

Abstract: Latar belakang. Penyandang thalassemia yang mendapat transfusi rutin tanpa kelasi besi yang optimal dapat menyebabkan kelebihan besi yang memicu stres oksidatif dan dapat mempercepat proses degenerasi di otak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…5 A previous study at Dr. Hasan Sadikin Hospital found that 67% of 10 to14-year-old patients had delayed growth. 7 Another study reported that more than half of thalassemia patients aged 13.8 and >15 years had delayed growth. The delayed growth and puberty might also occur in 12 to 17-year-old thalassemia patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 A previous study at Dr. Hasan Sadikin Hospital found that 67% of 10 to14-year-old patients had delayed growth. 7 Another study reported that more than half of thalassemia patients aged 13.8 and >15 years had delayed growth. The delayed growth and puberty might also occur in 12 to 17-year-old thalassemia patients.…”
mentioning
confidence: 99%
“…About 65 (81.2%) of the subjects had short stature (stunted and severely stunted, based on height-forage Z-score).Hashemi et al reported that 65.71% of thalassemia patients had short stature 15. Similarly, another study at the Thalassemia Clinic of Dr. Hasan Sadikin Hospital, Bandung on thalassemia patients aged 10-14 years found that 62% had short stature 7. Both studies assessed nutritional status using body mass index for age, with Hashemi et al reporting 81.4% normal and 18.6% malnourished subjects 15.…”
mentioning
confidence: 99%